Hemp reinforcement in lightweight geopolymers. (July 2018) - Galzerano, B; Formisano, A; Durante, M; Iucolano, F; Caputo, D; Liguori, B
Natural fibres have been widely studied as environment-friendly alternative to synthetic ones in composite manufacturing; they can be considered as reinforcement of geopolymeric foams for use as insulating materials. In this regard, the paper focuses on lightweight geopolymers reinforced with hemp fibre grids. These novel composite materials, produced in different ways, are characterized by means of wide experimental tests and their properties are compared with the ones of the plain geopolymer. Morphological analysis shows good bonding between the matrix and the hemp reinforcement; in addition, the main physical properties of the foam are not negatively affected by the presence of hemp fibres. From a mechanical point of view, the composites when subjected to quasi-static load conditions do not collapse in a brittle manner, and show improved flexural strength under dynamic load conditions. Finally, from thermal analysis, they guarantee a good thermal stability.